2017
DOI: 10.5812/ijp.9322
|View full text |Cite
|
Sign up to set email alerts
|

Non-Communicable Chronic Diseases: The Role of Neonatal Characteristics

Abstract: Background: Non-communicable chronic diseases (NCDs) are still the major cause of mortality and morbidity in young adults. Objectives: The aim of the study was to evaluate the influence of neonatal characteristics on NCD development. Methods: A questionnaire was assessed to evaluate the influence of cesarean section (CS), breastfeeding and prematurity on development of some NCDs. The questionnaire was distributed through an online form. Results: We received 6,379 responses. According to data, CS was not associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…This is a significantly higher prevalence in comparison to other European studies on children born at term, in which around 30% of children had EAR [2,16]. This high prevalence of EAR is significantly related to higher BMI at seven years of age and may possibly increase the risk of obesity and other non-communicable diseases in adulthood [17], as previously stated in a recent systematic review and meta-analysis in which childhood obesity was found to be a predictor of morbidity in adulthood [18].…”
Section: Discussionmentioning
confidence: 56%
“…This is a significantly higher prevalence in comparison to other European studies on children born at term, in which around 30% of children had EAR [2,16]. This high prevalence of EAR is significantly related to higher BMI at seven years of age and may possibly increase the risk of obesity and other non-communicable diseases in adulthood [17], as previously stated in a recent systematic review and meta-analysis in which childhood obesity was found to be a predictor of morbidity in adulthood [18].…”
Section: Discussionmentioning
confidence: 56%
“…Recently, other available data speculate that neonatal colonization contributes to other short- and long-term sequelae of prematurity, such as respiratory distress and bronchopulmonary dysplasia (BPD), retinopathy of prematurity (ROP) [67], somatic growth in early life, and cardiovascular and other non-communicable chronic diseases later in adulthood [68,69,70].…”
Section: Neonatal Dysbiosis and Consequences For The Premature Infmentioning
confidence: 99%
“…Afterwards, in childhood food preferences are formed and are tracked into childhood and beyond, and foundations are laid for a healthy adult life. 15 In our cohort, none of the investigated neonatal factors were associated to EAR. EAR in our cohort was not associated to gender, despite female obesity susceptibilities is a well-known phenomenon.…”
Section: Discussionmentioning
confidence: 55%